Deceptive responses: the impact of verbal and non-verbal countermeasures - Caso, Letizia (Legal and criminological psychology, 2006)
Objectives. This experiment investigates the impact of informing participants about verbal and non-verbal cues to deception on their verbal and non-verbal responses. Based on the fact that people are more practised in their verbal behaviour than in their non-verbal behaviour, we predicted that giving participants information about verbal cues would positively affect their verbal accounts resulting in them giving an account that appeared more credible. In contrast, we predicted that informing participants about non-verbal cues would have no noticeable effect on credibility. We also predicted that focusing on verbal behaviours would impair non-verbal performance and that, vice versa, concentrating on non-verbal behaviours would impair verbal performance, particularly in liars. Method. A total of 128 participants either told the truth or lied about the possession of an object. Prior to these interviews, participants were or were not informed about verbal cues to deception and were or were not informed about non-verbal cues of deception (these two factors were systematically manipulated). Results. As predicted, participants were able to adapt their verbal behaviour but were not able to change their non-verbal behaviour. However, focusing on one aspect (either verbal or non-verbal behaviour) did not occur at the expense of the other behaviour (either non-verbal or verbal). Conclusion. Verbal countermeasures may well be easier to apply than non-verbal countermeasures.